Analisis Biomekanika Gerak Boules Atlet Pétanque Menggunakan Teknologi Video Tracking untuk Evaluasi Kinerja - Anton Purnama (Yayasan Literasi Sains Indonesia, 2025)
The application of computer technology in athlete motion analysis has become an innovative approach to improving performance evaluation. This study aims to analyze the biomechanics of pétanque athletes' boules movements using video tracking technology as a performance evaluation tool. Pétanque is a precision sport that demands motor coordination, postural stability, and efficient throwing technique. By applying a digital-based video tracking method, athletes' movements are recorded and extracted into quantitative data such as joint angles, throwing velocity, and ball trajectory. This data is then analyzed using a biomechanical approach to identify optimal movement patterns and potential inefficiencies in individual techniques. The analysis results indicate a correlation between elbow flexion angle and throwing accuracy, as well as the importance of body rotation in supporting a stable throwing force. These findings provide practical insights for coaches and athletes in designing more focused and evidence-based training programs. This study also demonstrates the potential of video tracking technology as an effective, non-invasive tool to improve pétanque athletes' performance through objective and measurable movement evaluation.